Building Strong Brands in Retailing - Woodside, Arch; Walser, M. (Elsevier, 2007)
Brand strength is the relative power of attraction of a given brand versus other brands and the levels of other product attributes. “Brand” is an encompassing concept that includes retail firms as well as physical products and services. We propose and empirically test a behavior-based model of brand strength that is particularly relevant for competing retail enterprises. Eleven propositions in the model include the following points. P1: the brand strength of a given retailer is relative to the customer's desire for levels of other attributes, such as the names of competing retailers, specific price points, and performance characteristics built into competing products. P2: brand strength depends in large part on customer experience with a given retailer. P3: increasing customer experience decreases the impact of competitive contexts on brand strength. P4: a retailer's accessibility into working memory from long term memory influences brand strength. P5: a consumer's experience with a given retailer influences accessibility of the retailer from memory. A research method merging purchase histories with perceptual and judgment data was used to test the model. The results provide strong support for the propositions. The study includes an adaptation and empirical examination of Wind's [Wind (1977), “Brand Loyalty and Vulnerability,” in Consumer and Industrial Buying Behavior, Arch G. Woodside, Jagdish N. Sheth, and Peter D. Bennett, eds., New York: North-Holland] basic vulnerability matrix.